Product Attributes and Price on Purchase Decision of Xiaomi Smartphone - Satya, Adhitama; Irna, Cut (TRIKONOMIKA, 2016)
The aim of this study is to determine how the influence of product attributes and price on purchase decisions partially or simultaneously. This study used a sample of 100 respondents who are users of Xiaomi smartphones in Bandung, Jakarta, and Depok. Data analysis technique used in this study is descriptive analysis and multiple linear regression. Product attributes and price partially give positive and significant impact on purchasing decisions. Simultaneously, product attributes and price significantly give influence on purchasing decisions by 42.2%. It can be concluded that either partial or simultaneous attributes of the product and the price have significant impact on product purchasing decisions of Xiaomi smartphone.